CT analysis of frontal recess air cell and fluid dynamics simulation of frontal sinus in people with different frontal sinus development after Draf1–3 surgery - Zhu, Zhengru; Wang, Jian; Du, Weijia; Xu, Min; Xue, Tao; Lai, Yubing; Chen, Fuquan (European archives of oto-rhino-laryngology, 2024)
Objective To explore the effects of Draf1–3 on frontal sinus airflow and frontal sinus irrigation in people with different frontal sinus development Methods The development of the frontal sinus and the distribution of the frontal recess cells were evaluated by CT scan in 150 adults (300 sides). The airflow changes into the frontal sinus and frontal recess after Draf were analyzed by Fluent software under a steady state and quiet inspiratory state. Nasal irrigation after Draf in adults with well-developed frontal sinus was simulated using 120 mL saline at a rate of 12 mL/s in a position at 45° to observe the changes in transient flow distribution. Results The moderately developed type of the frontal sinus was the most common. The airflow patterns in the frontal sinus and frontal recess in the moderate development group were laminar, while several large vortexes were formed between the frontal sinus and frontal recess in the well-development group. The Draf exerted more significant effects on the patterns, pressure, and velocity of the airflow in the frontal sinus and frontal recess in the well development group than in the moderate development group. The volume fraction of saline in the frontal sinus increased significantly from Draf1 to Draf3, and the time required for a complete infiltration of saline in the frontal sinus mucosa was significantly reduced. Conclusions Draf1–3 has different effects on the airflow field of the frontal sinus with different developmental types; and Draf1–3 can significantly improve the postoperative flushing of the frontal sinus.